PET Imaging in a Case of the Semantic Variant of Primary Progressive Aphasia - Küper, M.; Zöller, M.; Liebeskind, S.; Wiltfang, J.; Benninghoff, J. (Fortschritte der Neurologie · Psychiatrie, 2013)
A 64-year-old right-handed Caucasian presented with a four-year history of word-finding deficits and otherwise fluent speech production. Neurological examination remained unremarkable apart from the word finding impairment. Likewise, neuropsychological evaluation confirmed significantly reduced semantic word fluency. While brain MRI depicted only discrete anterior temporal atrophy, 18-fluorodeoxyglucose PET showed clear hypometabolism of the anterior temporal pole bilaterally with left predominance. An imaging-supported diagnosis of the semantic variant of primary progressive aphasia was established in close accordance to recently published diagnostic criteria.The PET findings can be regarded as typical for this condition and PET imaging proved helpful to delineate other variants (non-fluent and logopenic) of primary progressive aphasia.
Keywords: frontotemporal dementia; neuroimaging; speech